2010
DOI: 10.3354/meps08420
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of viral shedding provide insights into the epidemiology of viral hemorrhagic septicemia in Pacific herring

Abstract: Losses from infectious diseases are an important component of natural mortality among marine fish species, but factors controlling the ecology of these diseases and their potential responses to anthropogenic changes are poorly understood. We used viral hemorrhagic septicemia virus (VHSV) and a laboratory stock of Pacific herring Clupea pallasii to investigate the kinetics of viral shedding and its effect on disease transmission and host mortality. Outbreaks of acute disease, accompanied by mortality and viral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 32 publications
2
37
0
Order By: Relevance
“…In addition to acute manifestations of VHS in Pacific herring which are well-documented (Kocan et al 1997, Hershberger et al 2006, 2007, 2010a, we found that the disease can also manifest in this species as a chronic form that is characterized by viral persistence within infected hosts for extended periods with nearbackground levels of VHS-specific host mortality (Fig. 1, Table 1).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In addition to acute manifestations of VHS in Pacific herring which are well-documented (Kocan et al 1997, Hershberger et al 2006, 2007, 2010a, we found that the disease can also manifest in this species as a chronic form that is characterized by viral persistence within infected hosts for extended periods with nearbackground levels of VHS-specific host mortality (Fig. 1, Table 1).…”
Section: Discussionmentioning
confidence: 93%
“…An apparent paradox exists when considering the persistence of VHSV in natural populations of Pacific herring where it is thought that high VHSV shedding rates from infected individuals contribute to virus perpetuation through a process of continuous transmission from infected to uninfected individuals (Kocan et al 2001, Hershberger et al 2010a). This means of perpetuation can only persist within a narrow range of the basic reproduction number (R 0 ), the average number of infected individuals resulting from a single infected host (Ostfeld 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular tools led to a better understanding of the differences among different VHSV strains, including virulence and host susceptibilities. The combined tools of the epidemiologist and the molecular virologist have clarified transmission dynamics of this pathogen and its rhabdovirus cousins, infectious haematopoietic necrosis virus and spring viraemia of carp virus [12][13][14]. Risk-based surveillance has controlled disease in aquaculture settings, resulting in the elimination of VHSV from Denmark's rainbow trout O. mykiss farms [15].…”
Section: Systems-based and Iterative Approach To Disease Diagnosis (Amentioning
confidence: 99%
“…After exposure to the virus and successful establishment of infection, Pacific herring and other species shed copious amounts of VHSV into the water (Kocan et al 1997;Hershberger et al 2010a;Kim and Faisal 2012). Shed VHSV can be detected in the water as early as 4-5 days postexposure (PE), prior to the onset of host mortality from the resulting disease.…”
Section: Principle #2: Pacific Herring Are Super-shedders Of Vhsvmentioning
confidence: 99%